CATALYTIC CONVERSION OF BIOGAS INTO SYNTHESIS GAS ON Ni, Co AND Ni-Co CATALYSTS - Baizhumanova T.S.,; Zhang Х.,; Murzin D.Y.,; Tungatarova S.A., (Academic Scientific Journal of Chemistry, 2020)
The world's oil reserves are shrinking every day due to continuous production and processing using the most modern technologies. Scientists around the world are looking for different types of raw materials and ways to use the vast resources of natural gas as a substitute for oil. In this regard, considerable attention is paid to natural and associated gas as an alternative source of raw materials for the petrochemical industry. In this paper, Ni, Co and Ni-Co catalysts carried to θ-Al2O3 prepared by the traditional method of air impregnation for moisture capacity are studied. The developed compositions of monometallic and bimetallic compositions of catalysts were studied by the XRD method. The efficiency of the dry methane reforming reaction was investigated in a stationary reactor under the optimal process conditions found experimentally: T = 700 and 900o C, GHSV = 6000 h-1 and CH4:CO2: Ar = 1: 1: 1.